2014
DOI: 10.1007/s00405-014-3420-9
|View full text |Cite
|
Sign up to set email alerts
|

Early and long-term morbidity after minimally invasive total laryngo-pharyngo-esophagectomy with gastric pull-up reconstruction via thoracoscopy, laparoscopy and cervical incision

Abstract: Total laryngo-pharyngo-esophagectomy (TLPE) with gastric pull-up reconstruction is still considered to be associated with major complications and a significant risk of in-hospital death. Minimally invasive esophagectomy, avoiding thoracotomy and laparotomy, has been increasingly performed for esophageal malignancies with the hope of reducing mortality and morbidity, such as pulmonary complications. The aim in this study was to assess early and long-term morbidity as well as treatment outcomes in patients treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…In these 2 patients, insertion of a tracheostomy tube was effective to improve tracheal stenosis. In cases in which tracheal stenosis cannot be avoided when tracheal necrosis improves, a tracheostomy tube should be inserted to treat tracheal stenosis [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…In these 2 patients, insertion of a tracheostomy tube was effective to improve tracheal stenosis. In cases in which tracheal stenosis cannot be avoided when tracheal necrosis improves, a tracheostomy tube should be inserted to treat tracheal stenosis [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…19 The free jejunal flap has many anatomical and physiological advantages in pharyngoesophageal reconstruction and is useful to bridge the gap between the gastric tube and the oropharynx. 19 Since Asamura et al 20 reported the first combined GP and a doubly looped free jejunal flap in a patient with synchronous double cancers, the literature 6,9,12,[20][21][22][23][24] has reported that 22 patients underwent a combined GP and free jejunal flap reconstruction. Three of them had an anastomotic fistula.…”
mentioning
confidence: 99%
“…Long-term survival analysis further indicated that compared with the OS results obtained with data from 1980 to 1999, a significant improvement was observed in CEC patients who underwent minimally invasive surgery from 2000 to 2013 (71.5 vs. 40.7%, P = 0.003). Other minimally invasive approaches, including total PLE ( 31 ), larynx-preserving hybrid surgery with endoscopic laryngopharyngeal surgery and open surgery ( 32 ) and larynx-preserving surgery ( 33 ), were also attempted, and satisfactory 2-year OS rates of 64.3, 71.5, and 50.6%, respectively, were achieved. In addition, primary RT and surgery have been directly compared in a large retrospective study ( 34 ).…”
Section: Discussionmentioning
confidence: 99%